Bioaccumulation and Tolerance Indices of Cadmium in Wheat Plants Grown in Cadmium-Spiked Soil: Health Risk Assessment - Halim, Md Abdul; Rahman, Mohammad Mahmudur; Mondal, Debapriya; Megharaj, Mallavarapu; Naidu, Ravi (Frontiers in Environmental Science, 2021)
Farmers use wastewater for irrigation in many developing countries, for example Bangladesh, India, China, Sri Lanka and Vietnam because they have limited access to clean water. This study explored cadmium (Cd) bioaccumulation in two spring wheat cultivars (cv. Mustang and Lancer), which were grown in different concentrations of Cd (0,1, 2, 4 and 8 mg kg-1) in agricultural soils. The half maximum inhibitory concentration (IC50) values were 4.21 ± 0.29 and 4.02 ± 0.95, respectively, whereas the maximum health risk index (HRI) was 3.85±0.049 and 5.33±0.271, respectively, for Mustang and Lancer. In other words, the malondialdehyde content increased significantly in Mustang (around five-fold) and Lancer (around four-fold) compared with the control treatment. Results revealed that Cd content was well above the acceptable limit (HRI > 1) in the two cultivars when exposed to different levels of Cd stress. The tolerant cultivar (Mustang) has potential to chelate Cd in the nonedible parts of plants in variable fractions and can be used efficiently to improve growth and macro- and micro-nutrients content while reducing Cd concentration in plants in Cd-contaminated soil. It can also diminish the HRI, which may help to protect humans from Cd risks. The two cultivars’ nutrient availability and sorption capacity significantly shape their survival and adaptability under Cd stress. Based on what is documented in the current study, we can conclude that Mustang is more tolerant and poses fewer health hazards to people than Lancer because of its capacity to maintain grain macro- and micro-nutrients under Cd stress.